The Role of Trust in Mediating the Influence of Perceived Value and Service Quality on Tenant Loyalty in Industrial Estates - Bayu Pamuji, Tri; Novandari, Weni; Pradisti, Larisa (Journal of Accounting and Finance Management, 2025)
This study aims to examine the effect of perceived value and service quality on tenant loyalty in an industrial estate, with trust as a mediating variable. The research was conducted using a quantitative approach, involving 100 tenant respondents from a selected industrial area in Central Java, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that perceived value and service quality have a significant direct effect on tenant loyalty. In addition, both variables significantly influence trust, which in turn positively affects tenant loyalty. Trust also plays a significant mediating role in the relationship between perceived value and service quality with tenant loyalty. These findings highlight the importance of building trust as a psychological bridge that transforms perceived value and service quality into sustainable tenant loyalty. This study contributes to the literature on business-to-business (B2B) relationship management and provides practical insights for industrial estate managers to strengthen tenant retention through trust-based strategies.